Chemokine-Induced Macrophage Polarization in Inflammatory Conditions - Ruytinx, Pieter; Proost, Paul; Van Damme, Jo; Struyf, Sofie (Frontiers in Immunology, 2018)
Macrophages represent a heterogeneous cell population and are known to display a remarkable plasticity. In response to distinct micro-environmental stimuli, e.g. tumor stroma versus infected tissue, they polarize into different cell subtypes. Originally, two subpopulations were defined: classically activated macrophages or M1, and alternatively activated macrophages or M2. Nowadays, the M1/M2 classification is considered as an oversimplified approach that does not adequately cover the total spectrum of macrophage phenotypes observed in vivo. Especially in pathological circumstances, macrophages behave as plastic cells modifying their expression and transcription profile along a continuous spectrum with M1 and M2 phenotypes as extremes. Here, we focus on the effect of chemokines on macrophage differentiation and polarization in physiological and pathological conditions. In particular, we discuss chemokine-induced macrophage polarization in inflammatory diseases, including obesity, cancer and atherosclerosis.